2019
DOI: 10.1080/13678868.2019.1656988
|View full text |Cite
|
Sign up to set email alerts
|

Talk-about talent: underlying philosophies on talent in Thai SMEs

Abstract: This paper provides insight into talent philosophies, the fundamental assumptions and beliefs about talent that are held by key decision-makers, in three award-winning Thai Small and Medium Enterprises (SMEs). Interviews were conducted with fifteen key decision-makers: the owner-manager of each SME and four managers the owner-manager identified as 'talent'. A discourse perspective informs the research and we draw on community of practice (CoP) theory as a heuristic device, enabling insights into decision-maker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Attracting talents, identifying, and designating persons as talents, training, developing and retaining talented staff featured prominently among SMEs' owners and managers as matters of pressing concern for them (Zamcu, 2014;Lizbetinova, 2015;Stokes et al, 2016;Lawless et al, 2019). The war for talent prompted by McKinsey's study has been one of the seminal works in TM studies (Beechler & Woodward, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Attracting talents, identifying, and designating persons as talents, training, developing and retaining talented staff featured prominently among SMEs' owners and managers as matters of pressing concern for them (Zamcu, 2014;Lizbetinova, 2015;Stokes et al, 2016;Lawless et al, 2019). The war for talent prompted by McKinsey's study has been one of the seminal works in TM studies (Beechler & Woodward, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, talents experience tensions when they need to operate in an egalitarian context where individual superiority is not embraced by other counterparts (Sumelius et al, 2020). The study by Lawless et al (2019) revealed that in the context of SMEs in Thailand, individuals promoted as talent did not act powerfully because of the expectations of relatives (who worked in the firm). Thus, the talent status was simultaneously perceived as a 'powerful' and 'powerless' position.…”
Section: Suppressingmentioning
confidence: 99%
“…The study of Kirk (2021) in the context of global talent mobility revealed that individuals refused to be labelled as a talent since this required them to be mobilized, causing detachment from their usual social life. The study by Lawless et al (2019) showed that talents declined promotions because of concerns with regard to envious people. These responses are examples of 'suppressing' tensions as one element is prioritized over the other.…”
Section: Passive Responsesmentioning
confidence: 99%
“…A conclusion to this could be that researching Learning in SMEs is not for the fainthearted and therefore we were delighted to see a significant response to our Call for Papers which has resulted in the six excellent papers herein. These not only cover a variety of topics, use various methodologies and are sited in different industries and geographic areas ranging from China (Mustafa, Elliott, and Zhou 2019) to Thailand (Lawless et al 2019), Hungary (Csillag et al 2019), the Republic of Ireland (Nolan and Garavan 2019) and Scotland (Cunningham and McGuire 2019), but they also consider some little explored aspects of owner-managers (e.g. Coetzer, Wallo, and Kock 2019), as well as the perspectives of employees.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Finally, Lawless et al (2019) Talk about Talent; Underlying Philosophies on Talent in Thai SMEs investigates the rarely explored area of talent management in SMEs, as well as being one of the few studies to focus on learning in SMEs in Thailand. It achieves this through qualitative interviews with fifteen key decision-makers from three awardwinning SMEs, drawing upon Lave and Wenger (1991) Communities of Practice theory.…”
Section: Overview Of This Special Issuementioning
confidence: 99%